UST GOZ KAPAGI TAM KAYIPLARINDA FRiCKE FLEP iLE ONARIM - AYGIT, A.Cemal; AYDIN, Yağmur; AYHAN, M.Semih; BAYÇIN, H.Nazmi (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Between May 1996-January 1998, four cases with total full-thickness upper eyelid defects resulted from tumor resection were reconstructed with Fricke flap. Oral mucosa graft was used for reconstruction of inner side of the eyelid. Results.- Complete eyelid closure and preservation of blink reflex were obtained in all patients at the postoperatiw examination. There was no corneal irritation symptoms. The results were satisfactory both aesthetically and functionally at the end of 21 months period of mean follow-up. Conclusion.- This technique is simple to perform, has a relatiwly low complication rate and produces a functional and aesthetically acceptable result.